Eugénie Paultre - matter of life - Paultre, Eugénie 1979- (HENI, 2021)
An epistolary collection of paintings by French painter and philosopher Eugenie Paultre, 'Matter of Life' is a diaristic account of the artist's six-month residency at Damien Hirst's workshop where she discovered and documented new possibilities in her painting, as well as a more profound connection to the work of her host.
Keywords: Paultre, Eugénie -- 1979-; Abstrakte Malerei; Paultre, Eugénie / 1980-; Painting, Abstract / 21st century; Color in art; Stripes in art; Bildband